The Influence of Work-Life Balance and Job Satisfaction on Turnover Intention Among Generation Z Employees at Four Points by Sheraton Jakarta, Thamrin - Renu Fara Dea; Youmil Abrian (Pt. Threeple Herphi Educate, 2025)
The hospitality industry plays a crucial role in tourism competitiveness, yet high turnover intention, particularly among Generation Z employees, remains a major challenge that threatens operational stability and increases recruitment costs. This study investigates the effect of work-life balance and job satisfaction on turnover intention among Generation Z employees at Four Points by Sheraton Jakarta, Thamrin. Using a quantitative design, data were collected from 43 respondents through structured questionnaires and analyzed with SPSS 25.0 using validity and reliability testing, classical assumption testing, and multiple linear regression. The findings show that work-life balance (β = –0.586, p < 0.001) and job satisfaction (β = –0.518, p < 0.001) both have significant negative effects on turnover intention. The model explains 81.6% of the variance (Adjusted R² = 0.816), highlighting that enhancing work-life balance and job satisfaction can substantially reduce turnover intention. These results provide theoretical contributions to employee retention studies and practical implications for human resource strategies in the hospitality industry.